The relationship between hand muscle strength and hand eye coordination with lower passing skills in volleyball extracurricular students of SMPN 1 Talegong - Gunawan, Asep; Solihin, Akhmad Olih; Syamsudar, Bangbang (ARKA INSTITUTE, 2025)
This study aims to determine the relationship between hand muscle strength and hand-eye coordination with underhand passing skills in volleyball extracurricular students at SMPN 1 Talegong. This study uses a quantitative approach with a correlational method. Data were collected directly during extracurricular training sessions through a series of tests conducted in sequence. Each student participated in a hand muscle strength test, a hand–eye coordination test, and an underhand passing skills test. The study sample consisted of 20 male students who actively participate in volleyball training. The results showed that the data were normally distributed and the relationship between variables was linear. The correlation test showed a positive and significant relationship between hand muscle strength and underhand passing skills, as well as between hand-eye coordination and underhand passing skills. In addition, the double correlation between hand muscle strength and hand-eye coordination with underhand passing skills was also significant. These findings indicate that increasing hand muscle strength and hand-eye coordination together can improve underhand passing skills in volleyball students. Therefore, it is recommended that volleyball training programs in schools emphasize the development of these two aspects to improve player performance. This research provides an important contribution to sports development, particularly in the development of volleyball underhand passing techniques.